Zur Vermehrung von Ooencyrtus kuwanae (Howard, 1910) unter Laborverhältnissen (Hymenoptera: Encyrtidae). - Schieferdecker, Helmut (Contributions to Entomology = Beiträge zur Entomologie, 1969)
Ooencyrtus kuwanae (Howard, 1910) can be grown in the laboratory on eggs of Lymantria dispar even if the latter have been sterilized. Their suitability as hosts decreases with increasing heat. They can be stored at +2°C for 35 days. The parasite can develop even in eggs from which the larvae are about to emerge if there are at least six days at 20°C between parasitation and the emerging of the larvae. - The parasites are attracted most by normal batches of eggs and least by sterilized and washed single eggs from which the hair has been removed. - As Ooencyrtus kuwanae in no stage survives the low winter temperatures in th GDR, it can hardly be introduced here with success. - Freshly emerged females reach the peak of their oviposition at 20°C on the fourth and fifth days of their lives. 95 per cent of all eggs are laid within eleven days. - The optimum temperature for the full utilization of the fertility is 21°C (with an average of 54 off spring per female). - The optimum density of parasites for mass breeding is five female parasites on 100 Lymantria eggs.